Active Inflammatory and Chronic Structural Damages of Sacroiliac Joint in Patients With Radiographic Axial Spondyloarthritis and Non-Radiographic Axial Spondyloarthritis - Tu, Liudan; Lin, Churong; Xie, Ya; Wang, Xiaohong; Wei, Qiujing; Zhang, Yanli; Gu, Jieruo (Frontiers in Immunology, 2021)
Objective: Evaluate the MRI evidence of active inflammatory and chronic structural damages in radiographic axial spondyloarthritis (r-axSpA) and non-radiographic axial spondyloarthritis (nr-axSpA). Methods: A retrospective review of 253 patients underwent sacroiliac joint (SIJ) MRI between June 2014 and December 2019 was performed. MRI images including short tau inversion recovery scan and T1 weighted spin echo scans were assessed using the Spondyloarthritis Research Consortium of Canada (SPARCC) score and SPARCC MRI SIJ structural score by two independent readers. Results: Higher mean score of inflammatory (SPARCC) was seen in r-axSpA patients when compared with nr-axSpA patients (8.08 vs 4.37, P<0.05). Frequencies of MRI structural lesions in r-axSpA patients and nr-axSpA patients were: erosion (65.84% vs 88.23%, P=0.002), backfill (33.17% vs 13.73%, P<0.001), fat metaplasia (79.21% vs 60.78%, P=0.01), and ankylosis (37.13% vs 1.96%, P<0.001). Patients with r-axSpA had a higher mean score for fat metaplasia (8.93 vs 4.06, P=0.0003) and ankylosis (4.49 vs 0.04, P<0.001). Conclusion: More active inflammatory and chronic structural damages except for erosion was seen in r-axSpA patients than nr-axSpA patients, while higher percentage of nr-axSpA patients present with erosion in MRI.